Milk yield and quality of Original Brown cattle reared in Italian alpine region. Issue 1 (14th December 2020) - Zanon, Thomas; Costa, Angela; De Marchi, Massimo; Penasa, Mauro; Koenig, Sven; Gauly, Matthias
Abstract: The present study aimed to investigate non-genetic sources of variation of milk production and quality traits of dual-purpose Original Brown (OB) cows farmed in Italian alpine region by using milk test-day records ( n  = 4034). Except for milk yield and somatic cell count, all phenotypes were predicted from milk mid-infrared spectra and included traditional composition traits, coagulation properties, casein fractions, minerals and fatty acids. Data were analysed using a mixed linear model which included calving season, parity, stage of lactation and first-order interactions as fixed effects, and cow and herd-test-date as random effects. Milk yield averaged 18.07 kg/d and means of fat, protein and casein content (%) were 4.03, 3.40 and 2.68, respectively. Primiparous OB cows produced milk with a greater content of unsaturated fatty acids compared with multiparous. Except for Na, minerals content was generally greater in primiparous than multiparous cows. The comparison with the literature demonstrated that OB cows produce milk with fatty acid profile similar to that of Alpine Grey and with more favourable coagulation properties and mineral composition than Pinzgauer cows. Considering that OB milk exhibited good coagulation properties, a prerequisite for cheesemaking, strategies to valorise this endangered breed should mainly focus on the manufacturing of OB mountain cheeses. In general, results for several milk-related performance coupled with the well-known strong adaptability of the breed to extensive mountain farming systems are the starting point towards the valorisation and potential expansion of this local dual-purpose genetic resource, with the ultimate goal of contributing to its conservation. Highlights: Primiparous cows showed greater mineral content compared to multiparous cows. The good milk coagulation properties and high α-CN and κ-CN of Original Brown cows milk are a prerequisite for cheesemaking efficiency. A greater content of unsaturated fatty acids was observed in primiparous than multiparous OB cows.